THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE'S PERFORMANCE IN COMMISSION GENERAL ELECTION BUKITTINGGI - Hariman Syaleh (Jurnal Apresiasi Ekonomi, 2019)
ABSTRACT This study aims to see "The Influence of Leadership Style and Work Motivation on Employee Election Performance of the City of Bukittinggi". The data analysis technique used is Multiple Linear Regression to determine the effect of the independent variables and dependent variables and the hypothesis test using the T test to test the significance level between the independent variables and the dependent variable. The results of this study indicate that the Leadership Style variable (X1) has a significant positive effect on employee performance with a calculated t value> from t table (4.504> 2.07) and a significance level of 0.000. While Motivation (X2) has a significant positive effect on employee performance with t count> t table (2.996> 2.07) and a significance value of 0.007. Together, leadership style and work motivation variables contributed 89.3% to employee performance and the remaining 10.7% was explained by other variables not discussed in this study. Keywords: Leadership Style, Motivation, Employee Performance.